n+(n+2)+(n+4)=-42

Simple and best practice solution for n+(n+2)+(n+4)=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n+(n+2)+(n+4)=-42 equation:


Simplifying
n + (n + 2) + (n + 4) = -42

Reorder the terms:
n + (2 + n) + (n + 4) = -42

Remove parenthesis around (2 + n)
n + 2 + n + (n + 4) = -42

Reorder the terms:
n + 2 + n + (4 + n) = -42

Remove parenthesis around (4 + n)
n + 2 + n + 4 + n = -42

Reorder the terms:
2 + 4 + n + n + n = -42

Combine like terms: 2 + 4 = 6
6 + n + n + n = -42

Combine like terms: n + n = 2n
6 + 2n + n = -42

Combine like terms: 2n + n = 3n
6 + 3n = -42

Solving
6 + 3n = -42

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3n = -42 + -6

Combine like terms: 6 + -6 = 0
0 + 3n = -42 + -6
3n = -42 + -6

Combine like terms: -42 + -6 = -48
3n = -48

Divide each side by '3'.
n = -16

Simplifying
n = -16

See similar equations:

| x+5=49 | | 4d+9-d-8= | | 12w+132=252 | | 36-4d=36-4d | | 5y+5=5x | | -3+7y=-66 | | 3x+9=-25+9x | | 5x-6y=120 | | 3(2z+4)=2(3z+10) | | 5x=5y+5 | | 3t+9=60 | | 8-x=7-2x+56 | | 9.25x+10.75x=300 | | 12+x=-12 | | 7x+4x+4+8=3x+3+7x | | 8-x=7-2x | | 12x^2+8x=20+5x | | 0.4(k+10)=0.6 | | 14=6c-8+5+3c | | x+7y=4 | | 2x-2(3-4x)+8=42 | | 4.5+p=-5.75 | | log[4](2x-15)-log[4](x-4)=1 | | 0=x^2-4x-30 | | Y=26+75x | | (3+2i)(3-2i)=0 | | y-3=-4(x+1) | | x(2x)=136 | | 3.6=0.9y | | -0.6(7-w)=-6 | | x^3+5x^2-16x-80= | | -2(-6)+8= |

Equations solver categories